EFFECT OF CAPITAL STRUCTURE AND LIQUIDATION ON FIRMS VALUE WITH PROFITABILITY AS INTERVENING VARIABLES (Case Study On Property And Real Estate Companies Registered In Indonesia Stock Exchange 2014-2019 ) - Elmi Aguduri Puspita; Indra Siswanti (Management Research Studies Journal, 2021)
This study aims to determine the effect of capital structure, liquidity on firm value with profitability as an intervening variable. The samples used in this study are companies engaged in property and real estate listed on the Indonesia Stock Exchange (IDX) for the period 2014 - 2019. The independent variables in this study are the current ratio (CR) and debt to equity ratio (DER) to price book value ratio (PBV) with return on equity (ROE). The number of samples used in the study amounted to 20 companies using purposive sampling. The results of this study indicate that the variable capital structure (DER) has no effect on firm value (PBV), liquidity (CR) affects firm value (PBV), capital structure (DER) affects profitability (ROE), Liquidity (CR) affects profitability (ROE), profitability (ROE) are unable to mediate the capital structure (DER) on firm value (PBV) and profitability is able to mediate between liquidity (CR) against firm value (PBV).